Transparansi Dan Akuntabilitas Pengelolaan Dana Desa Dalam Pemaknaan Masyarakat Desa Secara Kualitatif - Setyawati, Vincentia Devina; Yoseph Yustinianus Ferdinand, Deograsias (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The administration of the village government obtained an allocation of village funds since the enactment of Law Number 6 of 2014 concerning Villages. One of the village's income comes from the allocation of village funds that are part of the district/city balance fund. Therefore, the management of village funds should refer to the principle of managing state finances so they must be managed with the principles of transparency and accountability. Therefore, this study will analyze the community's understanding of transparency and accountability in the management of village fund finances, especially in the